围免疫抑制治疗期感染对重型再生障碍性贫血患者血液学反应及生存的影响 (Zhonghua Xue Ye Xue Za Zhi, 2015)
OBJECTIVE: To explore the effects of peri-immunosuppressive treatment (IST) infection on outcomes of severe and very severe aplastic anemia (SAA/VSAA) patients. METHODS: Medical record and follow-up data of 105 SAA/VSAA who underwent first-line IST were retrospectively analyzed to find out the characters of infections (1 month before to 3 months after IST), and its effects on hematologic response and survival. RESULTS: Of 105 patients, a total of 270 febrile episodes were recorded in 97 patients (92.4%) during their peri-IST periods, with the median infections of 2 (1–7) episodes in each patient with the median febrile duration of 7 (1–47) days. Respiratory system (35.1%) was the primary anatomic site of infection. Bacteria (88.2%) were common causes of total 169 pathogenic bacteria in 96 clear pathogenic bacteria episodes. And patients who got infection 1 month before IST had much lower 6-month hematologic response rate than their counterpart ones (50.8% vs 80.0%, P=0.004). Multiple febrile episodes (≥3 times) and the total febrile duration ≥4 days showed the best sensitivity and specificity according to the ROC curve analysis. The 5-year overall survival of the 105 patients was 76%. The 5-year OS of patients with multiple febrile episodes (≥3 times) were much lower than their counterpart ones [(59.6±7.2)% vs (89.5±4.0)%] (P <0.01). The 5-year OS of the total febrile duration ≥ 4 days was much lower than their counterpart ones [(63.4±5.8)% vs 100.0%] (P<0.01). CONCLUSION: Infections 1 month before IST were associated with hematologic response. Multiple febrile episodes (≥3 times) and infections with the febrile duration ≥4 days presented inferior hematologic response and survival.